Absorption in exoplanet atmospheres: Combining experimental and theoretical databases to facilitate calculations of the molecular opacities of water. (August 2021) - Kofman, Vincent; Villanueva, Geronimo L.
Highlights: A new method to reduce and apply large ab initio rovibrational databases is described. Line broadening parameters for water are collected and made available as a function of the rotational quantum number J. Ab initio rovibrational databases of H2O and HDO line lists are reduced and applied in radiative transfer calculations of exoplanet atmospheres. The detectability of HDO in an oxygen dominated atmosphere on Trappist-1 b is constrained for observations with JWST and LUVOIR. The high-temperature compatible line list is used to simulate high-resolution cross-correlation observations of hot Jupiter HD 189733b. Abstract: We developed a method to reduce large theoretical molecular rovibrational line lists to significantly shorter lists that capture both the morphology of the spectrum and the total opacity. Water is used as a test case: the routines are demonstrated using the state-of-the-art POKAZATEL (H2 O, 5.7 billion transitions) and VTT (HDO, 700 million transitions) databases. We validate the methods, and, using only 2.3 million transitions, we reproduce spectra from the full databases over the entire wavelength domain, at all resolutions, and in a fraction of the computational time that would be required were the full line lists used. As the variational line lists are applicable to much higher temperatures than commonly used experimentally-based databases, realistic simulations of high-temperature exoplanet atmospheres are possible. The approach is specifically developed to be applied in radiative transfer studies where larger line lists would result in prohibitively large calculation times. In addition to the light line lists, we collected collisional-broadening parameters of water in H2, He, CO2, and self-broadened, from several literature sources, and produced rotational quantum number dependent broadening tables, which can be used in combination with the line list to produce pressure broadened spectra for different atmospheres. The light line lists, in combination with the broadening parameters, allows the calculation of full Voigt line shapes in line-by-line, layer-by-layer calculations of radiative transfer models on personal computers. We demonstrate the new line lists in: 1) James Webb Space Telescope and Large UV/Optical/IR Surveyor simulations to detect HDO in an oxygen dominated atmosphere on Trappist-1 b and 2) simulated high-resolution emission spectra from HD 189733 b, constraining the water detectability using the cross-correlation method.